Screening of lactic acid fermentation by rhizopus oryzae on banana peel using two-level factorial analysis / Nurul Syafiqah Mohd Yaminudin ...[et al.] - Mohd Yaminudin, Nurul Syafiqah; Kamaludin, Atikah; Kamaruddin, Sharir Aizat; Aziman, Siti Nurbalqis; Mohd Zain, Nor Azimah; Ahmad Nasir, Nor Atikah Husna (Universiti Teknologi MARA, 2022)
For ages, pure sugars or edible crops have produced lactic acid. However, a major concern on lactic acid production lies in the cost of the raw materials used. Thus, an alternative to overcome this situation is urgently needed. Characterization of banana peels shows that it contains promising sugar that can be utilized for lactic acid production, which are xylose (0.774 g/L), glucose (0.756 g/L) and fructose (0.532 g/L). Thus, this study aims to screen the potential of banana peel as a substrate by using Rhizopus oryzae through batch fermentation for lactic acid production, as R. oryzae can synthesize lactic acid in low nutrient requirements. Two-level factorial analysis was designed to screen the effects of moisture content (60% and 80%), temperature (27 °C and 40 °C), pH (4.5 and 6.5) and inoculum size (1x104 spores/mL and 1x108 spores/g) on the lactic acid production. Based on the Two-level factorial (2LF) analysis, the highest lactic acid production of 0.0813 g/L was detected at 80 % moisture content, pH 4.5, the temperature of 27 °C and inoculum size of 1x104 spores/g. The findings show that most of the conditions have a significant difference between each other (p<0.05). Therefore, the fermentation of banana peels by R. oryzae could be a promising method to produce a lactic acid concentration.